Effect of repair in carbonated concrete with high water/cement ratio and shallow concrete cover. - Moreno, E.; Solís Carcaño, R.; Torres López, M. (Rev. Téc. Fac. Ing. Univ. Zulia)
Concrete carbonation affects the structure”™s service life. Even though there are well defined repair procedures, they are not widely known, thus employing a custom procedure. This investigation evaluated three repair procedures for reinforced concrete elements damaged by carbonation-induced corrosion, recreating critical conditions (high water/cement ratio and shallow concrete cover). Procedures A and B consisted in removing concrete at the rebar level (traditional procedure) before repair, adding a NaOH solution to the new concrete for procedure B. Procedure C consisted in removing contaminated concrete beyond the rebar level, placing new concrete without addition. Results show that due to the critical conditions recreated, none of the repair procedures allowed a significant increment of the structure”™s service life.